Comparing the fixational and functional preferred retinal location in a pointing task. (November 2015) - Sullivan, Brian; Walker, Laura
Abstract: Patients with central vision loss (CVL) typically adopt eccentric viewing strategies using a preferred retinal locus (PRL) in peripheral retina. Clinically, the PRL is defined monocularly as the area of peripheral retina used to fixate small stimuli. It is not clear if this fixational PRL describes the same portion of peripheral retina used during dynamic binocular eye–hand coordination tasks. We studied this question with four participants each with a unique CVL history. Using a scanning laser ophthalmoscope, we measured participants' monocular visual fields and the location and stability of their fixational PRLs. Participants' monocular and binocular visual fields were also evaluated using a computer monitor and eye tracker. Lastly, eye–hand coordination was tested over several trials where participants pointed to and touched a small target on a touchscreen monitor. Trials were blocked and carried out monocularly and binocularly, with a target appearing at 5° or 15° from screen center, in one of 8 locations. During pointing, our participants often exhibited long movement durations, an increased number of eye movements and impaired accuracy, especially in monocular conditions. However, these compensatory changes in behavior did not consistently worsen when loci beyond the fixational PRL were used. While fixational PRL size, location and fixation stability provide a necessary description of behavior, they are not sufficient to capture the pointing PRL used in this task. Generally, patients use a larger portion of peripheral retina than one might expect from measures of the fixational PRL alone, when pointing to a salient target without time constraints. While the fixational and pointing PRLs often overlap, the fixational PRL does not predict the large area of peripheral retina that can be used.